Education as a Predictor Factor for Knowledge of COVID-19 in Portugal - Gomes da Silva, Joana; Silva, Carla Sofia; Alexandre, Bárbara; Morgado, Pedro (Frontiers in Public Health, 2021)
COVID-19 is a major global Public Health. With this pandemics, several communication challenges arose, particularly with the emergence of the phenomenon called "infodemic" (e.g., the rapid production, spread and amplification of information - scientifically reliable or unreliable). This phenomenon, enhanced by higher consumption of information, is related with higher levels of disinformation, misinformation and malinformation, promoting states dominated by anxiety and fear, having a strong impact in mental health. Indeed, in Portugal, higher levels of consumption of information was found to be associated with poor mental health indicators. Health literacy is the ability of an individual to obtain, understand and use information to develop the skills to make free and informed decisions about one's health as well as assuming an active role in preventive medicine and in health policies, including the organizational and social context. Therefore, COVID-19 Health Literacy can facilitate distinguishing between correct or incorrect information on COVID-19 as well as empowering people to make informed and conscious decisions, and understanding and criticizing the advocated political measures, being a necessary act for effective behaviour change. This study aims to assess possible predictors of COVID-19’s Health Literacy - functional domain, using a questionnaire previously designed and validated and a mixed effects model. The present work highlights important findings, in order to create fruitful COVID-19’s health literacy promoting programs as well as provides scientific recommendations for COVID-19/pandemics prevention in the future.